Increasing Ca2+ accumulation in salt glands under salt stress increases stronger selective secretion of Na+ in Plumbago auriculata tetraploids - Duan, Yifan; Jiang, Liqiong; Lei, Ting; Ouyang, Keyu; Liu, Cailei; Zhao, Zi’an; Li, Yirui; Yang, Lijuan; Li, Jiani; Yi, Shouli; Gao, Suping (Frontiers in Plant Science, 2024)
Under salt stress, recretohalophyte Plumbago auriculata tetraploids enhance salt tolerance by increasing selective secretion of Na+ compared with that in diploids, although the mechanism is unclear. Using non-invasive micro-test technology, the effect of salt gland Ca2+ content on Na+ and K+ secretion were investigated in diploid and tetraploid P. auriculata under salt stress. Salt gland Ca2+ content and secretion rates of Na+ and K+ were higher in tetraploids than in diploids under salt stress. Addition of exogenous Ca2+ increased the Ca2+ content of the salt gland in diploids and is accompanied by an increase in the rate of Na+ and K+ secretion. With addition of a Ca2+ channel inhibitor, diploid salt glands retained large amounts of Ca2+, leading to higher Ca2+ content and Na+ secretion rate than those of tetraploids. Inhibiting H2O2 generation and H+-ATPase activity altered Na+ and K+ secretion rates in diploids and tetraploids under salt stress, indicating involvement in regulating Na+ and K+ secretion. Our results indicate that the increased Na+ secretion rate of salt gland in tetraploids under salt stress was associated with elevated Ca2+ content in salt gland.